The Progression and Shift from Sustainable to Regenerative Architecture Design Concept - Villacís-Ormaza, Marcelo (2023)
The buildings’ development and construction have contributed negatively over the years to the increase of the environmental footprint and have also affected the biosphere and society’s quality of life. For several decades the architectural discipline has studied various concepts and methods to mitigate and reduce these effects through sustainability until the concept of regenerative development. This process has been categorized by analyzing each era’s different paradigms, attributes, methodologies, and challenges through a timeline that allows us to know the causes of the evolution of sustainability in architecture. The literature review shows that another vision of how to understand sustainable architecture has emerged, making the concept serve as a relative means of raising awareness for the solution of environmental problems, where it is not the building regenerated as such, but rather the habitat processes that collectively focus on improving people’s lives through resilient ecological systems.